The papers of Henry Francis Fynn (Historia, 2021)
The   Natal   Archives   of   the   Republic    of   South   Africa,    which   formspart  of  the  state  archival   services  of  the  country  and  is  under  the  controlof   the   Director    of   Archives    in   Pretoria,    contains   a   large    number   ofinteresting    and   valuable    government   records    but    also   houses   severalimportant    collections    of   private    papers   which   are   the   property    of   thearchives  and  which,  under  certain   conditions,  are  available   to  researchers.In   the   category   of   private    collections    are   the   papers   which   areknown   to  students   as  the   Henry   Francis   Fynn   Papers.Henry   Francis   Fynn  was  one  of  the  earliest  British   pioneers   in  whatwas  later  to  become the  province   of  Natal  in  the  llepublic    of  South  Africa.He  was  born  in  1803  in  the  United   Kingdom   and  was  educated  at  Christ'sHospital,    London,   England. At   the   age  of   thirteen   he  found   his   wayto   Cape  Town   and   there   joined    his   father   who,   it   was   claimed,   hadvisited   the  port   of  Natal   as early  as  1806  on  a  voyage  from  Australia   tothe  Cape.    In   1818  Henry   Francis   Fynn   journeyed   to   Delagoa   Bay,   inPortuguese   East  Africa,    as  supercargo   on  a   commercial   speculation. Itwas  on  this   trip   that   Fynn   first   came  into   contact  with   the   Zulu   tribeswhich  then  inhabited   a  large  portion   of  Africa   South  of  the  Zambesi  River,and  it  was  then  that  Fynn  first   appreciated   the  possibilities   of  trade   withthe  interior   regions   of  Southern  Mrica.Back   in   Cape   Town,   he   joined    forces   with   a   certain    LieutenantFarewell   and   together   they  persuaded  the  Governor  of   the  Cape  Colonyto   grant   them  permission   to  trade   with   Natal.It   was  Fynn,   however,  who   reached  Natal   first   and   it   was  he  whodetermined   to   make  the   first    contact   with   the   great   Zulu   king,   Chaka,who  had  earned  the  reputation   of  being  the  Attila    of  Southern  Africa. Itis  very  possible   that  Fynn  was  the  first   white   man  to  be  seen by  Chaka.A   small    British    settlement,   mainly    concerned   with   trade   with   theZulus   of  the   interior,    was  soon  established   at  the   Bay,  near  the   presentthriving     port   of   Durban. This   settlement   was   continually    menaced  bythe   might   of   Chaka,  but   Fynn   was  able   to   ingratiate    himself    with   theZulu   chief   by  restoring   Chaka  to   health   after  his   arm  had   been  piercedby   an   enemy  spear.     This    ministration    saved  the   British    at  the   portfrom  Chaka's  ire  and  gained  for   Fynn  a  grant  of  land  almost  6,000  squaremiles   in   extent
Keywords: British pioneers; Zulus; Fynn; Henry Francis; Natal